2015
DOI: 10.1186/s13012-016-0376-8
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between pragmatic intervention design and theory: using behavioural science tools to modify an existing quality improvement programme to implement “Sepsis Six”

Abstract: BackgroundSepsis has a mortality rate of 40 %, which can be halved if the evidence-based “Sepsis Six” care bundle is implemented within 1 h. UK audit shows low implementation rates. Interventions to improve this have had minimal effects. Quality improvement programmes could be further developed by using theoretical frameworks (Theoretical Domains Framework (TDF)) to modify existing interventions by identifying influences on clinical behaviour and selecting appropriate content. The aim of this study was to illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 36 publications
2
59
0
Order By: Relevance
“…The use of available BCT × TDF domain mapping tools in a systematic review context represents a methodologically innovative aspect of this work and provides an example of how these recently developed tools may be further applied in secondary analyses of existing interventions. This systematic approach also demonstrates how these frameworks may be applied to identify limitations of, and missed opportunities in, the design of existing interventions, 221 and thus offers clear implications for future intervention refinement, design and research. In turn, this systematic approach has clear implications for future intervention design, refinement and research.…”
Section: Strengthsmentioning
confidence: 98%
“…The use of available BCT × TDF domain mapping tools in a systematic review context represents a methodologically innovative aspect of this work and provides an example of how these recently developed tools may be further applied in secondary analyses of existing interventions. This systematic approach also demonstrates how these frameworks may be applied to identify limitations of, and missed opportunities in, the design of existing interventions, 221 and thus offers clear implications for future intervention refinement, design and research. In turn, this systematic approach has clear implications for future intervention design, refinement and research.…”
Section: Strengthsmentioning
confidence: 98%
“…The current research utilises the Theoretical Domains Framework (TDF) ( Francis et al, 2012 ; Cane et al, 2012 ) which unites theoretical constructs from multiple behaviour change theories. The TDF classifies 14 domains including ‘Knowledge’, ‘Skills’, ‘Beliefs about capabilities’ and ‘Emotion’, known to influence behaviour and offer potential targets for change ( Steinmo et al, 2016 ). The TDF has been used to study a range of health professionals behaviours ( Fuller et al, 2014 ; Patey et al, 2012 ; Curran et al, 2013 ; French et al, 2012 ; Bussières et al, 2012 ) and offers ‘an inclusive, rather than selective, approach to exploratory research in the field of implementation’ ( Francis et al, 2012: 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…When the intervention aimed to increase implementation of an existing intervention, the target population was not those directly affected by the health issue. For example, Steinmo et al [46] set out to improve the implementation of the 'Sepsis Six' care bundle [47] because the target for use of the Sepsis Six bundle had not been reached within a UK hospital. In this instance, they viewed the target population as those in a position to implement 'Sepsis Six' rather than patients receiving the bundle.…”
Section: Action 2: Select the Intervention Development Approachmentioning
confidence: 99%
“…Developers working with high levels of stakeholder involvement identified a concern that the developed intervention might have limited transferability beyond the setting or group that contributed to its development. For example, Steinmo et al [46] observed that their collaborative approach was an important strength and a significant lever to the success of the intervention because it allowed the intervention to be shaped to the specific context; however, it was also a limitation because they could not draw conclusions about feasibility in other hospitals.…”
Section: Action 7: Involve Stakeholdersmentioning
confidence: 99%
See 1 more Smart Citation